Customer relationship management, brand image, social media instagram, dan efeknya terhadap keputusan pembelian produk jasa ALC Indonesia - Bahri , Khoirun Nisa; Baswarani , Delfta Tunjung; Santika, Santika (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine whether there is a significant relationship between customer relationship management, brand image and Instagram social media on purchasing decisions on ALC Indonesia's service products. This research is a quantitative research using a survey method. The nature of this research is descriptive and verification. In this study, the population taken was large and the size was not known with certainty. The number of samples proposed by using purposive sampling technique is as many as 100 respondents. Based on the research that has been done, it can be concluded that customer relationship management, brand image, Instagram social media influence the decision to purchase ALC Indonesia's service products. And customer relationship management through brand image influences the decision to purchase ALC Indonesia's service products and also Instagram social media through brand image influences the decision to purchase ALC Indonesia's service products.